Biographie W. A. Mozart's - Nissen, Georg Nikolaus von; Weber, Constanze 1763-1842; Feuerstein, Johann Heinrich 1797–1850 (Leipzig Breitkopf & Härtel, 1828)
Georg Nikolaus von Nissen (1761-1826) was a Danish diplomat and music historian. Nissen was married to Mozart's widow Constanze (née Weber; 1762-1842) and the author of one of the first biographies of the composer. The collection of the material was still in progress when Nissen died on 24 March 1826. Only the incomplete preface can be fully attributed to Nissen. The completion of the work, based on his notes, was left to a medical doctor and Mozart enthusiast living in Pirna, Johann Heinrich Feuerstein (1797–1850). Nissen deserves credit most of all for his efforts to collect all documents concerning Mozart, starting with the Mozart family's letters and including commemorative coins and monuments. Several critics (Solomon, Angermüller and Stafford) have called the work problematic and in some ways inaccurate, due to the editing of Nissen and Feuerstein, and some exaggerated statements of Constanze.
The book bears the date 1828, but according to Angermüller and Stafford it was published one year later, in 1829.
The inserted facsimile contains Mozart's handwriting of 'Das Veilchen', a song for voice and piano on a poem of Goethe.
Nach Originalbriefen, Sammlungen alles über ihn Geschriebenen, mit vielen neuen Beylagen, Steindrücken, Musikblättern und einem Fac-simile. Von Georg Nikolaus von Nissen, Königl. Dänischem wirklichen Etatsrath und Ritter vom Dannebrog-Orden etc. etc. Nach dessen Tode herausgegeben von Constanze, Wittwe von Nissen, früher Wittwe Mozart. Mit einem Vorworte vom Dr. Feuerstein in Pirna.
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; 19th Century (1801-1900); Biography; Correspondence; Composer; Pianist; Violinist; Austria